Development of formulations containing smectitic clay and biogenic carbonate sand from Porto Santo island for the preparation of cleansing and whitening facial masks - Pena-Ferreira, Maria Rosa; Santos, Delfim; Silva, João Baptista Pereira; Amaral, Maria Helena; Sousa-Lobo, José Manuel; Gomes, Jorge Hamilton; Gomes, Celso de Sousa Figuerido (Anales de Hidrología Médica, 2012)
Facial masks are considered as being the oldest cosmetic preparations used for beauty purposes. Clays besides of being used as excipients (with emulsifying, gelifying, and thickening properties due to colloidal characteristics) are used as active ingredients in such preparations. Both smectitic clay and biogenic carbonate sand of Porto Santo’ island, Madeira archipelago, show specific properties which have allowed their traditional use for skin care as well as for the treatment of diseases of the rheumatic, orthopedic and physiatric systems. Based upon the traditional knowledge of the application sand in the natural space (beach, or more precisely in the dry and warm sand of the transition zone beach-frontal dune), and more recently in Geomedicine Clinics, the present study aimed at the design of formulations to be applied in dermocosmetics. Formulations were developed containing the association biogenic carbonate sand plus smectitic clay (bentonite) from Porto Santo ‘island in order to be used for skin cleansing and whitening. To characterize both the physical and mechanical properties of the developed masks texture and viscosity tests were carried out. Tests of cutaneous biometry were carried out too to assess pH, lipids content, and hydration for formulations characterization in terms of efficacy of its application for dermocosmetic purposes. The developed facial masks containing smectitic clay, biogenic carbonate sand and Aloe Vera from Porto Santo’ island exhibit adequate consistency for cutaneous application and show good degreasing and whitening properties.